Evolution of the population status of prawn Cryphiops caementarius on Cañete river (2000-2015) - Wasiw G., José (2017)
Based on surveys in the Cañete river (Peru) in the period 2000-2015, information concerning fisheries and biological aspects of the population of fresh water prawn Cryphiops caementarius is reported. Also, physicochemical parameters of water quality were determined to establish the relationship between these and resource distribution throughout the watershed prospected. The main results indicate a minimum fraction of individuals with above 120 mm size (<5%). According to the analysis of the «b» parameter of the length-weight relationship, the evaluated population will be composed of individuals with a higher weight relative to their size, higher proportion of male specimens, and higher density and mean biomass in the lower altitudinal strata. The density and average biomass resource calculated for the Cañete river tends to recover after the critical situation reached in 2012. Oral knowledge of increased fishing pressure, illegal fishing and anthropogenic alterations in river basins evaluated was noted.